Characterization of Streptomyces Cell Surface by the Microbial Adhesion to Solvents Method - Zanane, C.; Mitro, S.; Mazigh, D.; Lekchiri, S.; Hakim, T.; El Louali, M.; Latrache, H.; Zahir, H. (International Journal of Microbiology, 2023)
The cell surface physicochemical properties of Streptomyces should influencing the dispersal and adsorption of spores and hyphae in soil and should conditioning there interactions with organic or metal substances in the bioremediation of contaminated environment. These properties are concerning surface hydrophobicity, electron donor/acceptor, and charge surface. To date, only hydrophobicity of Streptomyces was studied by contact angle measurements and microbial adhesion to hydrocarbons (MATH). In this work, we studied the electron donor/acceptor character of the Streptomyces cell surface in two ionic strength 10−3 M and 10−1 M of KNO3. Thus, to facilitate the characterisation of the surfaces of microbial cells, we used a simple, rapid, and quantitative technique, the microbial adhesion method to solvents (MATS), which is based on the comparison of the affinity of microbial cells for a monopolar solvent with a polar solvent. The monopolar solvent can be acid (electron acceptor) or basic (electron donor), but both solvents should have a surface tension similar to that of the Kifshitz van der Waals components. At the significant ionic strength of the biological medium, the electron donor character is well expressed for all 14 Streptomyces strains with very significant differences among them ranging from 0% to 72.92%. When the cells were placed in a solution with a higher ionic strength, we were able to classify the donor character results into three categories. The first category is that the weak donor character of strains A53 and A58 became more expressed at 10−1 M KNO3 concentration. The second category is that three strains A30, A60, and A63 expressed a weaker character in a higher ionic strength. For the other strains, no expression of the donor trait was obtained at higher ionic strength. In a suspension with a concentration of 10−3 KNO3, only two strains expressed an electron acceptor character. This character is very important for strains A49, A57, A58, A60, A63, and A65 at 10−1M KNO3. This work has shown that these properties vary greatly depending on the Streptomyces strain. It is important to consider the change in physicochemical properties of surface cells with ionic strength when using Streptomyces in different bioprocesses.